Surgical management of acute subdural haematomas: current practice patterns in the United Kingdom and the Republic of Ireland. (June 2013) - Kolias, A. G.; Scotton, W. J.; Belli, A.; King, A. T.; Brennan, P. M.; Bulters, D. O.; Eljamel, M. S.; Wilson, M. H.; Papadopoulos, M. C.; Mendelow, A. D.; Menon, D. K.; Hutchinson, P. J.; et al.
Abstract Introduction. Uncertainty remains as to the role of decompressive craniectomy (DC) for primary evacuation of acute subdural haematomas (ASDH). In 2011, a collaborative group was formed in the UK with the aim of answering the following question: "What is the clinical- and cost-effectiveness of decompressive craniectomy, in comparison with craniotomy for adult patients undergoing primary evacuation of an ASDH?" The proposed RESCUE-ASDH trial (Randomised Evaluation of Surgery with Craniectomy for patients Undergoing Evacuation of Acute Subdural Haematoma) is a multicentre, pragmatic, parallel group randomised trial of DC versus craniotomy for adult head-injured patients with an ASDH. In this study, we used an online questionnaire to assess the current practice patterns in the management of ASDH in the UK and the Republic of Ireland, and to gauge neurosurgical opinion regarding the proposed RESCUE-ASDH trial. Materials and methods. A questionnaire survey of full members of the Society of British Neurological Surgeons and members of the British Neurosurgical Trainees Association was undertaken between the beginning of May and the end of July 2012. Results. The online questionnaire was answered by 95 neurosurgeons representing 31 of the 32 neurosurgical units managing adult head-injured patients in the UK and the Republic of Ireland. Forty-five percent of the respondents use primary DC in at least 25% of patients with ASDH. In addition, of the 22 neurosurgical units with at least two Consultant respondents, only three units (14%) showed intradepartmental agreement regarding the proportion of their patients receiving a primary DC for ASDH. Conclusion. The survey results demonstrate that there is significant uncertainty as to the optimal surgical technique for primary evacuation of ASDH. The fact that the majority of the respondents are willing to become collaborators in the planned RESCUE-ASDH trial highlights the relevance of this important subject to the neurosurgical community in the UK and Ireland.